Health research priorities in medical thesis at National University of Piura, 2010-2014 - Purizaca-Rosillo, Nelson (2016)
Objective: To determine the frequency of thesis to obtain the medical degree at the National University of Piura (UNP) whose aim was framed within the Peru's national and/or Piura's regional HRP from 2010 to 2014. Material and Methods: A cross-sectional study was conducted. All thesis to obtain the medical degree registered at the library of the UNP and the specialized library of the human medicine faculty from 2010 to 2014 were included. According the aim of the thesis, it was determined if it was related to a national or regional HRP. We searched through Google Scholar if the thesis that met with a HRP had been published in a scientific journal. Results: 150 thesis were found in the study period. Only 15 (10%) thesis had as the main objective a national HRP and 1 (0.6%) a regional HRP. Besides, none of the thesis had been published. Conclusion: There is a low frequency of medical thesis that were framed within a national and/or regional HRP.